Peran Media Sosial sebagai Strategi Pemasaran pada Sewa Kostum Meiyu Aiko Malang - Premi Wahyu Widyaningrum (Al Tijarah, 2016)
Marketing Strategies with utilize Advancement of Information Technology have impact financially efficient and practically process, with using social media can create the best result. Promoting business using social media which are free cost and can attract new customers social media user, this things very suitable if applied in SME (Small Medium Enterprises) business. This research aims to explore the utilization of social media as marketing strategy for Small and medium enterprises (SMEs). Qualitative approach with the case study is used as research design. Researchers using in-depth interview to the owner of Meiyu Aiko in Malang. The results showed that the Marketing Strategy through social media and website for the promotion of costum rent’s service in Malang can build a strong relationship between management of Meiyu Aiko with consumers both online and offline. Promotional activities can easily provide brand awareness and can be transmitted by social media followers to users of other social media. This research also emphasize social media as online advertising that could be used as marketing strategy in today’s digital era.